Neurological soft signs and grey matter abnormalities in individuals with ultra-high risk for psychosis - Kong, Li; Herold, Christina; Schröder, Johannes (PsyCh journal, 2019)
Neurological soft signs (NSSs), conventionally defined as subtle neurological abnormalities, are frequently found in individuals with schizophrenia. Many neuroimaging studies have also reported that NSSs are associated with grey matter changes in patients with schizophrenia at different stages of the illness. However, these findings may be confounded by the effect of antipsychotic medications, chronicity, and duration of untreated psychosis. Examining NSSs in individuals with ultra-high risk (UHR) for psychosis may help to identify the neuroanatomical substrates of NSSs related to the illness itself and to avoid these potential confounding effects. A sample of 21 individuals with UHR were included in the present study.
First published: 04 December 2018
Gesehen am 17.01.2020